Modeling optical transmissivity of graphene grate in on-chip silicon photonic device - Amiri, Iraj Sadegh; Ariannejad, Mohammad Mahdi; Jalil, Muhammad Arif; Ali, Jalil; Yupapin, Preecha Promphan (Elsevier, 2018)
A three-dimensional (3-D) finite-difference-time-domain (FDTD) analysis was used to simulate a silicon photonic waveguide. We have calculated power and transmission of the graphene used as single or multilayers to study the light transmission behavior. A new technique has been developed to define the straight silicon waveguide integrated with grate graphene layer. The waveguide has a variable grate spacing to be filled by the graphene layer. The number of graphene atomic layers varies between 100 and 1000 (or 380 nm and 3800 nm), the transmitted power obtained varies as ∼30% and ∼80%. The ∼99%, blocking of the light was occurred in 10,000 (or 38,000 nm) atomic layers of the graphene grate.